(untitled) (Research, Society and Development, 2025)
This paper aims to show how literacy and literacy are fundamental in basic education. While literacy focuses on decoding, literacy allows students to understand the meaning of texts within a social context. Literature is a powerful tool for developing reading and writing skills, helping students to appropriate language and express their ideas. In a class with a 3rd grade class, the legend of Curupira was explored, connecting it to environmental preservation. The collective reading of the legend and creative activities, such as drawings and comic strips, were proposed to stimulate reflection on the importance of nature. The activity provided a space for students to express their understanding and promote a meaningful connection with their experiences, highlighting the importance of orality and Amazonian literature in the educational context.